Retrospective of the peruvian education since 1972 and perspectives to the year 2021 “Bicentennial of Our Independence” - Ruiz Durán, Graciela (2017)
The present article consists of three parts: the first part related to a retrospective vision of Peruvian education, it focuses on the Peruvian Educational Reform undertaken since 1972. The second part will be focused on the quality of higher  education, within the National Evaluation, Accreditation and Certification of Educational Quality System - SINEACE, Act N° 28740 and the recent University Act. The third part will draw a prospective view of education, which is required in the celebration of the Bicentennial of our independence as the Peruvian Republic, in the year 2021.